Identifying governance strategies that effectively support ecosystem services, resource sustainability, and biodiversity. - Kenward, R; Whittingham, M; Arampatzis, S; Manos, B; Hahn, T; Terry, A; Simoncini, R; Alcorn, J; Bastian, O; Donlan, M; Elowe, K; Franzén, F; et al. (2011)
Conservation scientists, national governments, and international conservation groups seek to devise, and implement, governance strategies that mitigate human impact on the environment. However, few studies to date have systematically investigated the performance of different systems of governance in achieving successful conservation outcomes. Here, we use a newly-developed analytic framework to conduct analyses of a suite of case studies, linking different governance strategies to standardized scores for delivering ecosystem services, achieving sustainable use of natural resources, and conserving biodiversity, at both local and international levels. Our results: (i) confirm the benefits of adaptive management; and (ii) reveal strong associations for the role of leadership. Our work provides a critical step toward implementing empirically justified governance strategies that are capable of improving the management of human-altered environments, with benefits for both biodiversity and people.